Market Value of Industrial Equities - Smith, Edgar Lawrence (The Review of Economics and Statistics, 1927)
to a movement of five points in a high-priced stock as to a five point change in one selling at a low figure, more serious error tends to creep into the picture whenever some of the companies whose stocks are used as a basis for calculating the average price level issue rights to subscribe to additional stock or declare stock dividends, either in terms of their own shares or through the distribution of shares in subsidiary companies. Any change in the character of the equities represented, affects the validity of charts based on the average market quotations of a list of stocks. Those whose concern it is to protect investments in common stocks, need some more reliable measure of changes in the value of common stock equities, and it was with the purpose of establishing such a measure that the present studies were undertaken. As a result of